Student Attendance Information System using Telegram Bot API and Visual Basic 6.0 - Hariono, M.Kom, Tholib; Aris Widya, Moh. Anshori; Yaqin, Nurul (KH. A. Wahab Hasbullah University, 2022)
Student delinquency is a form of student behaviour that deviates from school rules. One of them is truant or irregular entry. Skipping behaviour that is left will give a tendency for students to commit other violations such as brawls, using drugs, free sex and others. Monitoring trusting students is not easy because routine communication between parents and the school is needed. This study aims to create a system to facilitate communication between schools and parents by implementing a fire bot telegram using the long polling method. The system is made using Visual Basic 6.0, consisting of two main parts, namely the attendance system and bot telegram management. The attendance system handles student attendance consisting of fingerprint registration and attendance scans, while the telegram bot management handles the sending of attendance information consisting of telegram ID registration, attendance information and permit information. The test results show the process of taking and sending information via telegram bot runs fast, in the test register of the parent telegram ID the time required is an average of 5.6 seconds, sending scanned student attendance information 4.25 seconds and sending permit information on average 7, 07 seconds.